A Comparative Study on the Antibacterial Activity of Artemisia dracunculus and Ocimum basilicum Essential Oils on Multidrug Resistant Bacteria Isolated from Ready to Eat Foods. Issue 3 (4th May 2018) - Sharafati Chaleshtori, Reza; Taghizadeh, Mohsen; Mazroii Arani, Navid; Sharafati Chaleshtori, Farhad
Abstract: The aim of this study was to determine the antibiotic resistance pattern in E.coli and Salmonella isolated from ready to eat (RTE) foods such as hamburger, salad, frozen vegetable, traditional ice cream, halva and kebab and their sensitivity to Artemisia dracunculus and Ocimum basilicum essential oils (EOs). The antibiotic resistance of 18 E.coli and 2 Salmonella obtained isolates were determined by Kirby Bauer method. Also, susceptibility of the obtained isolates were evaluated by micro-dilution and agar disk diffusion methods to EOs. All of the E. coli isolates were resistant to amoxicillin/clavulanic acid, ampicillin, nitrofurantoin, tetracycline, kanamycin and gentamycin. Two Salmonella isolates were found to be resistant to amoxicillin/clavulanic acid, ceftazidime, kanamycin, ceftriaxone and chloramphenicol. The antibacterial activity of Ocimum basilicum EO was higher than Artemisia dracunculus EO against multi-drug resistance (MDR) bacteria. MDR Salmonella isolates were more susceptible to EOs than MDR E. coli . Therefore, the above EOs could be used as a potential source of natural antibacterial agents against MDR bacteria in food.